2020
DOI: 10.3390/biom10101357
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Metabolism in Glioblastoma and Metastatic Brain Tumors: A Review of Sphingomyelinases and Sphingosine-1-Phosphate

Abstract: Glioblastoma (GBM) is a primary malignant brain tumor with a dismal prognosis, partially due to our inability to completely remove and kill all GBM cells. Rapid tumor recurrence contributes to a median survival of only 15 months with the current standard of care which includes maximal surgical resection, radiation, and temozolomide (TMZ), a blood–brain barrier (BBB) penetrant chemotherapy. Radiation and TMZ cause sphingomyelinases (SMase) to hydrolyze sphingomyelins to generate ceramides, which induce apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 186 publications
(222 reference statements)
1
34
0
Order By: Relevance
“…Many studies have suggested that the SphK1/S1P axis could play a role in the promotion of several types of tumors, based on the overexpression of SphK1 in tumor cell lines and in patient samples, and sometimes, on the measured increased S1P levels in tumors and/or in patient blood. These studies have recently been reviewed for breast [ 46 ], ovarian, [ 47 ], and gastrointestinal cancers [ 48 ], hepatocellular carcinoma [ 49 ], melanoma [ 50 ] and glioblastoma [ 51 ]. High S1P in breast tumor tissue is significantly associated with lymphnode metastasis [ 52 ].…”
Section: Sphingolipids In Cancermentioning
confidence: 99%
“…Many studies have suggested that the SphK1/S1P axis could play a role in the promotion of several types of tumors, based on the overexpression of SphK1 in tumor cell lines and in patient samples, and sometimes, on the measured increased S1P levels in tumors and/or in patient blood. These studies have recently been reviewed for breast [ 46 ], ovarian, [ 47 ], and gastrointestinal cancers [ 48 ], hepatocellular carcinoma [ 49 ], melanoma [ 50 ] and glioblastoma [ 51 ]. High S1P in breast tumor tissue is significantly associated with lymphnode metastasis [ 52 ].…”
Section: Sphingolipids In Cancermentioning
confidence: 99%
“…Activation of S1PRs results in cellular proliferation and further production of S1P to promote cell motility and survival. This tight linkage of interconnected pathways for the rapid synthesis and breakdown of ceramide (pro-apoptotic) and S1P (pro-survival) has given rise to the "sphingolipid rheostat" model, in which the balance of these two biomolecules plays an important and potentially targetable role in normal cellular function and oncogenesis (127)(128)(129)(130)(131).…”
Section: Altered Phospholipid Metabolismmentioning
confidence: 99%
“…In gliomas, this shift is likely due to multiple alterations in sphingolipid synthesis, including increased expression of SK1 (134)(135)(136), deletion of c h r o m o s o m a l r e g i o n s c o n t a i n i n g S P L ( 1 3 7 ) , a n d downregulation of S1P phosphatase 2 (138), resulting in increased S1P levels; as well as inhibition of ceramide synthase (139) and increased expression of ceramidases (134). The activity of SMases in glioblastoma is still being elucidated, but it has been shown that acid SMase may sensitize glioma cells to chemotherapy and radiation by increasing metabolism of sphingomyelin to ceramide and consequent apoptosis in the context of p53-deficiency; conversely, neutral SMase may be involved in increasing ceramide production in p53-wildtype cells (129). Increased understanding of the proapoptotic role of SMases in glioblastoma may yield new therapeutic targets.…”
Section: Altered Phospholipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells can evade apoptosis by converting ceramide to sphingosine-1-phosphate. In this regard, Hawkins et al [ 24 ] discuss the role of sphingomyelinases and sphingosine 1-phosphate in glioblastoma and metastatic brain tumors. There are two main types of sphingomyelinases: neutral and acid.…”
mentioning
confidence: 99%